One-Step Posterior and Anterior Combined Approach for L5 Retroperitoneal Schwannoma Eroding a Lumbar Vertebra - Giancarlo D’Andrea; Giovanni Sessa; Veronica Picotti; Antonino Raco (Case Reports in Surgery)
We report the case of a large lumbar schwannoma eroding the vertebra and originating from spinal canal with invasion of the retroperitoneal space. We also review all the cases in literature reporting lumbar schwannomas eroding the vertebral bodies and invading the retroperitoneal space focusing on the surgical strategies to manage them. Spinal CT-scan revealed a 44 mm×55 mm inhomogeneous soft-tissue mass arising from the right L5-S1 neural foramen and its most anterior portion had a clear colliquative aspect. Magnetic resonance image showed a neoplastic lesion with homogeneous low signal in T1WI, heterogeneous signal in T2WI, and strong enhancement in postgadolinium examination. It developed as well in the retroperitoneal space, posteriorly to the iliac vein, up to the psoas muscle with wide erosion of the omolateral conjugate foramen. We performed a one-step combined approach together with the vascular surgeon because the lesion was too huge to allow a complete resection via a posterior approach and furthermore its tight relationship with the psoas muscle and the iliac vessels in the retroperitoneal space should be more safely managed via a retroperitoneal approach. We strongly suggest a 1-step surgery first approaching the dumbbell and the intraspinal schwannomas posteriorly achieving the decompression of the spinal canal and the cleavage of the tumor cutting the root of origin and the vascular supply and valuating the stability of the spine for potential artrodesis procedure. The patient must be then operated on via a retroperitoneal approach achieving the complete en bloc resection of the tumor.